Sintilimab induced ICIAM in the treatment of advanced HCC: A case report and analysis of research progress - Ji, Hongxiang; Wen, Zhijian; Liu, Bin; Chen, Hongbiao; Lin, Qian; Chen, Zhan (Frontiers in Immunology, 2022)
Immune checkpoint inhibitor-associated adverse reactions (irAEs) are a clinical treatment issue that requires additional attention when ICIs have significant survival benefits in patients with advanced hepatocellular carcinoma (HCC). Among them, ICIs-associated myocarditis (ICIAM) is a kind of severe irAE with a high mortality rate (17%–50%). Despite its low incidence (PD1/PD-L1 related: 0.41%–0.8%), ICIAM can significantly disturb the decision making of therapeutic schemes and even the survival outcomes of patients. ICIAM induced by sintilimab has not been reported in any complete clinical studies yet and understanding the clinical characteristics involved may inform better practices for the management. Here, we reported a 78 y/o patient with advanced HCC, who experienced ICIAM induced by sintilimab within a short course from treatment onset and found that adequate baseline examination before the implementation of the therapeutic scheme, regular monitoring of myocardial enzymonram and cardiac imaging were measures for the early detection, while glucocorticoid pulse therapy is still the best choice with timely and sufficient application. Simultaneously, the combination of other immunosuppressants may lead to better results. New-predictive markers and examination methods are still required to facilitate the early detection.